Head-on collision of ion acoustic solitary waves in an electron-positron-ion plasma with superthermal electrons - Chatterjee, P.; Ghosh, U.N.; Roy, K.; Muniandy, S.V.; Wong, C.S.; Sahu, B. (American Institute of Physics, 2010)
The head-on collision of ion acoustic solitary waves in a three-component unmagnetized plasma with cold ions, Boltzmann distributed positrons, and superthermal electrons is investigated using the extended Poincare-Lighthill-Kuo method. The effects of the ratio of electron temperature to positron temperature, the spectral index, kappa, of the electron kappa distribution, and fractional concentration of positron component (p) on the phase shift are studied. It is found that the presence of superthermal electrons play a significant role on the collision of ion acoustic solitary waves. (C) 2010 American Institute of Physics.[doi:10.1063/1.3528544]